Konsep Mahram dalam Al-Quran (Implikasinya Bagi Mobilitas Kaum Permpuan di Ranah Publik) - Mustaqim, Abdul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
This article describes the concept of mahram in the Qur' an. The word mahram is mentioned 83 times in the Qur'an, and it relates or addresses to various issues: from food, bank interest to kinships. This present study discusses the mahram concept in its relation to kinship in which marriage between the designated kin is for bidden. Mahr am has been usually associated with the restrictions of women travelling alone, without accompanying mahram. However, such restriction is not found in the Qur' an but in the hadus literature. Nowadays women have participated in public affairs and traveled around the world. How shall we reconcile the idea of mahram in the Qur'an, hadits and social contexts of our time? This study suggests that the Qur'anic idea of mahram is for maintaining the familial chain particularly among those for whom marrying each other is not permissible. It is not for prohibiting women from travelling. In the latter concern, the the guarding of women's safety might be replaced by social system.